Wacana Kekerasan Fisik dalam Komik Jurnalistik Footnotes in Gaza - Ridhani Agustama; Anang Hermawan (Program Studi Ilmu Komunikasi, 2014)
Conflict between Israel and Palestine still become the hot issue that all media covering on it. But the information flow about the conflict is dominated by Western Media. The domination followed by Western Media’s effort to manipulate the information. For example, Western Media called Palestine as a dispute land; meanwhile if we look at the history it was the Israel colonized Palestine.There are several alternative point of view about the conflict. One of the alternative point offered by Joe Sacco, an US comic writer. Sacco offers the stories from fact that often forgotten by the Western Media. This research discuss about Footnotes in Gaza, one of Sacco’s comic. Footnotes in Gaza based on Sacco’s investigation about Khan Younis and Rafah incident in 1956, when the the Palestine civilian were being killed by Israeli soldiers.This research use Sara Mills’ positioning the subject-object as the methods. In The Footnotes in Gaza, clearly seen that the position of the narrator (the subject) is always held by the victims (the Palestinians), while the object is the Israeli with all their act of violence.